2010
DOI: 10.1016/j.breast.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Breast lesions with ultrasound imaging-histologic discordance at 16-gauge core needle biopsy: Can re-biopsy with 10-gauge vacuum-assisted system get definitive diagnosis?

Abstract: The aim of this study was to evaluate if re-biopsy with 10-gauge vacuum-assisted biopsy (VAB) could get definitive diagnosis for breast lesions with ultrasound (US) imaging-histologic discordance at 16-gauge core needle biopsy (CNB). From January 2007 to June 2008, a consecutive biopsy was performed on 1069 lesions with US-guided 16-gauge CNB. A total of 28 lesions were considered to be US imaging-histologic discordant and all of them underwent subsequent 10-gauge VAB. All malignant lesions located at VAB were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…[15][16][17][18] Among lesions with ultrasonographyehistologic discordance, 21.4% are upgraded in the pathological diagnosis after VAB, according to Li et al 19 Furthermore, it has also been reported that VAB might be valuable for definitive diagnosis when pathological results with CNB are discordant with imaging findings. [19][20][21] Accordingly, the use of VAB is supported by many physicians, especially for small lesions. 14,22,23 However, we have to keep in mind that VAB is based on the same concept as CNB: a partial sampling of the tumor.…”
Section: Discussionmentioning
confidence: 93%
“…[15][16][17][18] Among lesions with ultrasonographyehistologic discordance, 21.4% are upgraded in the pathological diagnosis after VAB, according to Li et al 19 Furthermore, it has also been reported that VAB might be valuable for definitive diagnosis when pathological results with CNB are discordant with imaging findings. [19][20][21] Accordingly, the use of VAB is supported by many physicians, especially for small lesions. 14,22,23 However, we have to keep in mind that VAB is based on the same concept as CNB: a partial sampling of the tumor.…”
Section: Discussionmentioning
confidence: 93%
“…For the biopsy detection of calcifications, VAB was more sensitive in obtaining calcifications in both mass lesions and non-palpable lesions. In the detection of malignancy and calcification, VAB in general showed a better performance, either alone [19] or combined with hook wire localization [20,21]. One should, however, note that residual cancer could still be present even with VAB removal of all microcalcifications [12].…”
Section: Discussionmentioning
confidence: 99%
“…22,51,58 VAB has also gained recognition lately as an approach to manage patients after BPs without atypia are diagnosed on automated needle biopsy specimens, hence sparing a subset of patients from surgery. 47,54,5962 Experience is still accumulating in this regard.…”
Section: Discussionmentioning
confidence: 99%